Lymphocyte-to-monocyte ratio before chemoradiotherapy represents a prognostic predictor for locally advanced rectal cancer - Deng, Yu-Xiang (Onco Targets Ther, 2017)
Research indicates that cancer-triggered inflammation plays a pivotal role in carcinogenesis. Here, we aimed to evaluate the correlation of lymphocyte-to-monocyte ratio (LMR) before neoadjuvant chemoradiotherapy (CRT) with clinical outcomes in patients with locally advanced rectal cancer (LARC). We retrospectively enrolled 317 consecutive patients with LARC between 2004 and 2013. The optimal cutoff values of LMR were determined using receiver operating curve analysis. Overall survival (OS) and disease-free survival related to the LMR were analyzed using the log-rank test and multivariate Cox regression methods. We found that a low LMR (≤4.91) was prominently correlated with worse prognostic features and a shorter 3-year survival rate of LARC. Moreover, multivariate Cox analysis revealed that elevated LMR was an independent factor for better OS (hazard ratio 0.538, 95% confidence interval 0.292–0.991, P=0.047). In addition, univariate logistic regression analysis showed that the LMR was not associated with tumor pathologic regression. In conclusion, LMR is identified as a valuable prognostic marker for predicting the OS of LARC patients receiving CRT.